1983
DOI: 10.1002/zaac.19834990424
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen an oxidischen Katalysatoren. XXXIV. Redoxverhalten des Nickels in NiNaY‐Zeolithen 1. Reduzierbarkeit und Reoxydierbarkeit von Nickel in NiNaY‐Zeolithen

Abstract: Die Eigenschaften von metallischem Nickel in reduzierten (470–870 K) und reoxydierten (470, 670 K) NiNaY‐Proben wurden durch chemische Analyse (Reaktion mit K2Cr2O7) und spektroskopische Untersuchungen (FMR, IR nach CO‐Chemisorption und UV/VIS) charakterisiert. Die Reduktion der Ni2+‐Kationen oxidischer Cluster erfolgt einstufig, während isoliert lokalisierte Ni2+‐Kationen über Ni+‐Kationen zum Metall reduziert werden. Entsprechend der Lokalisierung und dem Austauschgrad ändert sich der Reduktionsgrad des Nick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
3
8
0
Order By: Relevance
“…In agreement with data from the literature, ,, the bands at 2220 and 2212 cm -1 are assigned to Ni 2+ −CO species. Here, the carbonyls are much more stable than the Ni 2+ −CO carbonyls detected with the Ni/SiO 2 sample.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…In agreement with data from the literature, ,, the bands at 2220 and 2212 cm -1 are assigned to Ni 2+ −CO species. Here, the carbonyls are much more stable than the Ni 2+ −CO carbonyls detected with the Ni/SiO 2 sample.…”
Section: Resultssupporting
confidence: 89%
“…Adsorption of CO on a Ni/SiO 2 sample activated at 773 K results in formation of a band at 2192 cm -1 , which decreases in intensity with the equilibrium pressure and disappears after evacuation. In agreement with data from the literature, ,, the band at 2192 cm -1 is assigned to Ni 2+ −CO species.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…It is shown that under identical experimental conditions the degree of reduction follows the order zeolite X > zeolite Y and mordenite > zeolite Y.2,4 While the coexchanged cations determine the overall chemical properties of the zeolites through the average electronegativity,5 they also compete with Ni2+ for exchange sites. Thus, under the same experimental conditions the degree of reduction of Ni2+ in alkaline-earth-exchanged Y exceeds that of NiNa-Y and follows the order Mg < Ba < Sr < Ca.4 However, the degree of reduction in NiNaX exceeds that of NiCaX.6 In X-type zeolites Ce3+ is known to promote the reduction of Ni2+, while La3+ retards it.7-10 In the presence of acidic OH groups the reduction of Ni2+ is difficult, because the equilibrium Ni2+ + H2 ^Ni(0) + 2H+ (1) is driven to the left.4…”
Section: Introductionmentioning
confidence: 99%